Efektivitas media pembelajaran audio visual terhadap keterampilan teknik dasar bulu tangkis - Cendra, Romi; Gazali, Novri; Dermawan, M. Rian (Universitas Nusantara PGRI Kediri, 2019)
The purpose of this study was to know the effectiveness of audio-visual media towards badminton basic technical skills of Penjaskesrek students of Islamic University of Riau. This study used an experimental quasi method with pre-test and post-test design. The form of research design used in this study was Pretest-Posttest Design Control Group. This research was conducted at Islamic University of Riau from May to September 2018. The data collection method used in this study was using test and measurement techniques, and the test instrument was basic badminton skills test. The population in this study was the active Penjaskesrek students of Islamic University of Riau in the academic year of 2015/2016 with a number of 219 students from 8 classes. The sampling in this study was conducted by using purposive sampling technique. The samples taken were only two classes from eight classes, namely 4C and 4G. 4C class, 19 students was the experimental class group while the 4G class, 22 students was the control class. The data collected from the results of the initial and final tests were analyzed by using normality test, homogeneity test and t-test statistics. The conclusion in this study was that the audio visual learning media provided significant effectiveness towards badminton basic technical skills of Penjaskesrek students of Islamic University of Riau, where the results obtained by tcount (10.64) which was greater than ttable (1,734).